EVOLUTION OF HIGH-FREQUENCY TRADE - Ol'ga A. Grishina (Plekhanov Russian University of Economics, 2018)
Present day exchange trade using computer algorithm (or high frequency robots) that can make independent trade decisions and function without man’s involvement is becoming quite usual. Intensive technological upgrading of finance markets fostered the development of high-frequency trade, thus ways of conducting trade transactions were transformed. In line with technology development the speed of transactions being carried out by high-frequency robots increased considerably during the last two decades. The majority of research dealing with assessment of highfrequency trade impact mention the wide spread of the latter and, consequently the growth in its market share, especially on stock exchanges. At the same time the drawback of various research is the limited analysis of reasons for high-frequency trade popularity and preconditions of its evolution. Apart from this many researchers neglected the fact that the development of high-frequency trade was promoted not only by technological evolution of computer systems but by legislative regulation, first of all in the USA. High-frequency trade was initially developed on US stock exchange and even today it is actually the only one news-maker in the field. The article reviews the key stages of exchange trade development, which foster establishment and evolution of high – frequency trade and shows legislative initiatives that caused its popularity. The authors present arguments for and against highfrequency trade and analyze current legislative initiatives that disclose potential trend aimed at the development of the system regulating high-frequency robots’ functioning.